THE INFLUENCE OF INFRASTRUCTURE ON FOREIGN DIRECT INVESTMENT IN INDONESIA - Agustine Nirmalasari Putri; Ida Ayu Meisthya Pratiwi (Adisam Publisher, 2025)
Foreign Direct Investment (FDI) refers to capital investment made by foreign entities in a host country through the establishment or acquisition of a company, with the intention of directly managing and controlling the business operations. The growth of FDI in a country can be influenced by various factors, one of which is infrastructure development. This study aims to analyze the influence of road, telecommunications, electricity, and clean water infrastructure on Foreign Direct Investment (FDI) in Indonesia, both simultaneously and partially. The study was conducted in Indonesia over a 21-year observation period from 2003 to 2023. The dependent variable is foreign direct investment in Indonesia, while the independent variables include total road length, number of telephone connections, volume of distributed electricity, and volume of clean water supply. This study employs a literature review approach using secondary data and applies descriptive analysis and multiple linear regression techniques. The results indicate that, simultaneously, all four infrastructure variables significantly affect FDI in Indonesia. However, partially, only the volume of clean water shows a statistically significant influence on FDI. The variables of road length, telephone connections, and electricity distribution do not exhibit significant effects. These findings suggest that basic infrastructure such as clean water plays a crucial role in attracting foreign investment, while traditional infrastructure indicators need to be re-evaluated in the digital era. Therefore, enhancing the quality and accessibility of infrastructure particularly basic infrastructure that supports industrial needs constitutes an essential strategy for promoting FDI growth in Indonesia.